1994
DOI: 10.1016/s0022-5347(17)35124-8
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Pyelolithotomy

Abstract: Retroperitoneal laparoscopic pyelolithotomy was successful in 5 of 8 patients using the recently described balloon technique of retroperitoneal laparoscopy. All patients were considered for this new minimally invasive procedure only on economic grounds. However, with improved technique and instrumentation, the retroperitoneal laparoscopic approach could become a practical alternative for the management of patients with medium sized pelvic stones not amenable to extracorporeal shock wave lithotripsy nor ideally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 5 publications
1
48
0
2
Order By: Relevance
“…The outcomes of LP were firstly published by Gaur et al [17] LP performed for the management of staghorn stones was also reported by Gaur et al [18] . In a meta-analysis conducted in 2013, the authors considered PNL, and LP as safe, reliable, and effective treatment modalities in large solitary stones bigger than 2 cm, and reported demonstrated shorter operative, and hospital stay times, lesser blood loss, and less frequent postoperative febrile states for PNL procedures.…”
Section: Discussionmentioning
confidence: 90%
“…The outcomes of LP were firstly published by Gaur et al [17] LP performed for the management of staghorn stones was also reported by Gaur et al [18] . In a meta-analysis conducted in 2013, the authors considered PNL, and LP as safe, reliable, and effective treatment modalities in large solitary stones bigger than 2 cm, and reported demonstrated shorter operative, and hospital stay times, lesser blood loss, and less frequent postoperative febrile states for PNL procedures.…”
Section: Discussionmentioning
confidence: 90%
“…A third non-randomized controlled trial by Gaur and colleagues 23 reported a mean operative time of 116 minutes for LPL, compared with 152 minutes for PNL (p value not stated). The longer time of LPL in our study was usually related to the long learning curve of LPL as well as the time needed for intracorporeal suturing and delivery of the stone.…”
Section: Discussionmentioning
confidence: 99%
“…Importance of laparascopic pyelolithotomy was known after the study of Gaur et al (14). Laparoscopic pyelolithotomy is an alternative method for PNL.…”
Section: Discussionmentioning
confidence: 99%